Relaxation, de Vries behavior, and layer contraction in chiral liquid crystal by dielectric spectroscopy. Issue 3 (3rd July 2018) - Zoghaib, W.M.; George, A.K.; Carboni, C.; Surekha, M.; Ashok Kumar, A.V.N.; Chalapathy, P.V.; Potukuchi, D.M.
ABSTRACT: Low-frequency (LF) (20 Hz to 10 MHz) field response investigations are reported in TSiKN65F series-based chiral liquid crystal compound, C-10, viz., 1-[3ʹ-nitro-4ʹ-S-(2-decyloxy)phenyl]phenyl-4-(1, 1, 1, 3, 5, 5, 5-heptamethyltrisiloxydecyloxy)-3-Fluorobenzoate. Molecular frame with 10-methylene units and a chiral center on one end is connected to the core with 3-phenyl rings. Other end of core connected to biforked trisiloxy chain to promote de Vries phase. Isotropic-smectic-A and smectic-A-smectic-C*deVr transitions are determined by capacitance study. DC field reversal and polarized optical microscopy textures confirmed occurrence of SmC*deVr phase below SmA. Hysteresis is observed in SmC*deVr . Tilt order parameter growth estimated in SmC*deVr phase through β equal to 0.673 agrees with mean field prediction. Relaxation behavior in kilo Hertz region is explained through longitudinal dipole moment μl reorientation. Dynamics studied through LF dielectric relaxation infers dominance of order director fluctuations at few kilohertz. Higher activation energy in de Vries phase infers greater degrees of freedom and additional constraints. Loss ε″(T) exhibited anomalous trend at SmA-to-SmC*deVr interface. Temperature variation of tilt θ(T) is estimated from loss. Loss in de Vries phase gets suppressed by field to infer collective response. Curie–Weiss behavior by γ-exponent ~0.03 infers weaker ferroelectric response in SmC*deVr phase. Loss variation ε″(T) addressed by perturbed bookshelf model reveals marginal layer contraction by <1% in SmC*deVr phase. Estimates of layer shrinkage through R- and f-parameters in SmC*deVr phase confirm the de Vries behavior.